Microencapsulation And Application Of Catha Edulis Extract On Sexual Behaviour, Body Weight And Blood Lipid Profiles In Rats - Abdulaziz, Hesham Hasan Hussein (2011)
Catha edulis (CE) which is commonly known as khat has been reported to improve sexual motivation and has anti-obesity property. Khat is traditionally consumed via chewing of the leaf followed by slowly swallowing the juices for the desired effect. This study aimed to simulate the sustained release of khat content through the preparation of sustained release microcapsules of khat extract. The effect of khat extract and the sustained release microcapsules on the sexual motivation, vaginal secretions, estradiol levels, food intake, body weight, blood cholesterol and triglycerides levels was examined in rats.